Cooperative Learning Model To Improve Students' Learning Motivation In Tahfizhul Qur'an Learning In MIN 7 of Southwest Aceh - Nurbayani; Ashariatul Fitri; Nurma (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Learning motivation plays a crucial role in the success of Tahfizhul Qur’an programs, yet conventional teacher-centered approaches often limit student engagement and reduce intrinsic motivation. This study aims to analyze the implementation and effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model in enhancing students’ learning motivation in Tahfizhul Qur’an learning at MIN 7 Aceh Barat Daya. A qualitative case study design was employed to obtain an in-depth understanding of the learning process. Data were collected through interviews, observations, and documentation involving teachers and students who participated in STAD-based learning. The findings reveal that the implementation of the STAD model was carried out through structured stages, including the formation of heterogeneous groups, collaborative memorization activities, teacher facilitation, and evaluation through individual quizzes and group rewards. These processes significantly increased students’ learning motivation, as indicated by higher interest, active participation, improved collaboration, and better learning outcomes. In addition, positive competition among groups contributed to strengthening students’ enthusiasm in memorizing and understanding Qur’anic verses. However, several challenges were identified, including differences in students’ memorization abilities, limited instructional time, insufficient learning resources, and the need for adaptation to cooperative learning methods. This study concludes that the STAD cooperative learning model is effective in fostering a more interactive and motivation-oriented learning environment in Tahfizhul Qur’an education, although its optimal implementation requires adequate resource support, flexible time management,and targeted assistance for students with lower abilities